Differences of Perceived Image Generated through the Web Site: Empirical Evidence Obtained in Spanish Destinations - Blazquez-Resino, Juan J.; Muro-Rodriguez, Ana I.; Perez-Jimenez, Israel R. (Frontiers in Psychology, 2016)
In this paper, a study of the perceived destination image created by promotional Web Pages is expounded in an attempt to identify their differences as generators of destination image in the consumers’ mind. Specifically, it seeks to analyse whether the web sites of different Spanish regions improve the image that consumers have of the destination, identifying their main dimensions and analysing its effect on satisfaction and intentions of the future behaviour of potential visitors. To achieve these objectives and verify the hypotheses, a laboratory experiment was performed, where it was determined what changes are produced in the tourist´s previous image after browsing the tourist webs of three different regions. Moreover, it analyses the differences in the effect of the perceived image on satisfaction and potential visitors´ future behavioural intentions. The results obtained enable us to identify differences in the composition of the perceived image according to the destination, while confirming the significant effect of different perceived image dimensions regarding satisfaction. The results allow managers to gain a better understanding of the effectiveness of their sites from a consumer perspective as well as suggestions to follow in order to achieve greater efficiency in their communication actions in order to improve the motivation of visitors to go to the destination.